2018
DOI: 10.1016/j.ijfatigue.2018.05.027
|View full text |Cite
|
Sign up to set email alerts
|

A more effective rationalisation of fatigue crack growth rate data for various specimen geometries and stress ratios using the CJP model

Abstract: A more effective rationalisation of fatigue crack growth rate data for various specimen geometries and stress ratios using the CJP model

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…These applications include the determination of ΔK, crack closure, J-integral, crack tip plastic zones 33,34 and stress intensity factors defined by the CJP crack tip field model. 35 DIC is used here to obtain CTOD versus load plots by locating two points behind the crack tip. The location of these two points is a critical aspect in the interpretation of CTOD measurements and its subsequent application to FCG.…”
Section: Application To Dic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These applications include the determination of ΔK, crack closure, J-integral, crack tip plastic zones 33,34 and stress intensity factors defined by the CJP crack tip field model. 35 DIC is used here to obtain CTOD versus load plots by locating two points behind the crack tip. The location of these two points is a critical aspect in the interpretation of CTOD measurements and its subsequent application to FCG.…”
Section: Application To Dic Resultsmentioning
confidence: 99%
“…Yates et al 32 provided an overview of some applications of DIC in characterizing full‐field elastic–plastic crack tip displacement fields. These applications include the determination of Δ K , crack closure, J ‐integral, crack tip plastic zones 33,34 and stress intensity factors defined by the CJP crack tip field model 35 . DIC is used here to obtain CTOD versus load plots by locating two points behind the crack tip.…”
Section: Application To Dic Resultsmentioning
confidence: 99%
“…A recently published paper [27] demonstrates that the CJP model provides an effective rationalisation of fatigue crack growth data across several geometries of Grade 2 titanium specimens and various stress ratio values, with the added advantage that the usual geometric compliance correction factors are not necessary in the calculation of the CJP stress intensity factors. Additionally, calibration curves were derived that related the parameters ΔA, ΔB and ΔD in the CJP stress intensity factors KF and KR to values of the standard ΔK.…”
Section: Progress In the Development Of The Cjp Modelmentioning
confidence: 99%
“…The relationship between ΔD and ΔK for DENT specimens could be fitted with either a quadratic or a linear equation. The authors concluded that the CJP model of crack tip fields can simultaneously provide insight into the underlying mechanisms of plasticity-induced shielding and predict the effective driving force for fatigue crack growth, characterised by ΔKCJP [27]. It therefore offers a powerful advantage in fatigue life prediction by explicitly incorporating plasticity-induced shielding forces and, through a modification to include Mode II loading, can potentially deal with roughness-induced closure [22].…”
Section: Progress In the Development Of The Cjp Modelmentioning
confidence: 99%
“…Experimental verification of the concepts in the CJP model followed a little more slowly than the theoretical developments, reflecting factors such the complexity of phase-stepping photoelastic fatigue experiments, the development of software necessary to automate the CJP model solution from photoelastic and DIC images, and the training of PhD students. Over the last several years, however, researchers from the University of Jaen in Spain, Gifu University in Japan, Southwest Jiaotong University and Xiamen University in China have been making considerable progress in experimental verification of the model [6,7] This paper will summarise the results obtained to date and which demonstrate that the CJP model appears capable of providing an improved correlation of fatigue crack growth rates across a range of stress ratios and specimen geometries, compared with the standard stress intensity factor calculations. The model also appears to correctly characterise both plastic zone shape and size and this paper will also briefly discuss the data obtained from overload experiments.…”
Section: Introductionmentioning
confidence: 99%